Entacapone Treatment Modulates Hippocampal Proteins Related to Synaptic Vehicle Trafficking - Dae Young Yoo; Hyo Young Jung; Woosuk Kim; Kyu Ri Hahn; Hyun Jung Kwon; Sung Min Nam; Jin Young Chung; Yeo Sung Yoon; Dae Won Kim; In Koo Hwang (Cells, 2020)
Entacapone, a reversible inhibitor of catechol-O-methyl transferase, is used for patients in Parkinson’s disease because it increases the bioavailability and effectiveness of levodopa. In the present study, we observed that entacapone increases novel object recognition and neuroblasts in the hippocampus. In the present study, two-dimensional electrophoresis (2-DE) and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry were performed to compare the abundance profiles of proteins expressed in the hippocampus after entacapone treatment in mice. Results of 2-DE, MALDI-TOF mass spectrometry, and subsequent proteomic analysis revealed an altered protein expression profile in the hippocampus after entacapone treatment. Based on proteomic analysis, 556 spots were paired during the image analysis of 2-DE gels and 76 proteins were significantly changed more than two-fold among identified proteins. Proteomic analysis indicated that treatment with entacapone induced expressional changes in proteins involved in synaptic transmission, cellular processes, cellular signaling, the regulation of cytoskeletal structure, energy metabolism, and various subcellular enzymatic reactions. In particular, entacapone significantly increased proteins related to synaptic trafficking and plasticity, such as dynamin 1, synapsin I, and Munc18-1. Immunohistochemical staining showed the localization of the proteins, and western blot confirmed the significant increases in dynamin I (203.5% of control) in the hippocampus as well as synapsin I (254.0% of control) and Munc18-1 (167.1% of control) in the synaptic vesicle fraction of hippocampus after entacapone treatment. These results suggest that entacapone can enhance hippocampal synaptic trafficking and plasticity against various neurological diseases related to hippocampal dysfunction.